Comparing Auditory and Visual Electrophysiological Markers of Consciousness in Bimodal Stimuli - Ahmad, Asfa (My University, 2026)
Neural correlates of consciousness indicate specific neural processes that are linked to conscious experiences. Auditory awareness negativity (AAN) and Visual awareness negativity (VAN) have been suggested as the candidates of early sensory processing while, Lateral positivity (LP) is believed to reflect the post perceptual processing like attention, decision making and response selection. This study investigated the auditory and visual electrophysiological markers of consciousness in bimodal conditions using a GO/NOGO task. Participants were asked to report their perceptual awareness of near threshold auditory and visual stimuli while the EEG was recorded. Because of the ongoing nature of the larger project, the current study examines specifically unattended, non-target bimodal trials, allowing the examination of awareness related neural activity while reducing the response related confounds. Results showed that both AAN and VAN are consistently differentiated aware from unaware stimuli across auditory and visual modalities, with differences in latency and their topographical distributions. On the other hand, LP effects were less consistent and varied across modalities suggesting its role in post perceptual processing rather than awareness. Overall, these findings suggest that AAN and VAN are related to early sensory processing, whereas LP reflects later cognitive processing.
Keywords: Key words: Neural Correlate of Consciousness (NCC); awareness; attention; Auditory awareness negativity (AAN); Visual awareness negativity (VAN); Lateral Positivity (LP); GO/NOGO task; Sensory discrimination task.